Hemorrhagic Thrombocytopathy with Platelet Thromboxane A2 Receptor Abnormality: Defective Signal Transduction with Normal Binding Activity - Ushikubi, Fumitaka; Okuma, Minoru; Kanaji, Kenji; Sugiyama, Tateo; Ogorochi, Toshiya; Narumiya, Shuh; Uchino, Haruto (Thrombosis and Haemostasis, 1987)
Subnormal platelet responses to thromboxane A2 (TXA2) were found in a patient with polycythemia vera, and the mechanism of this dysfunction was analyzed. The patient’s platelets showed defective aggregation and release reaction to arachidonic acid, enzymatically generated TXA2 and synthetic TXA2 mimetics (STA2, U-46619). In contrast, they showed normal responses to thrombin. When the platelet TXA2 receptor was examined with both a 125I-labelled derivative of a TXA2 receptor antagonist ([125I]-PTA-OH) and a 3H-labelled TXA2 agonist ([3H]U-46619), the equilibrium dissociation rate constants (Kd) and the maximal concentrations of binding sites (Bmax) of the patient’s platelets to both ligands were within normal ranges, suggesting that the binding capacity of their TXA2 receptor was normal. STA2 failed to induce normal elevation in the. cytoplasmic free calcium ion concentration, phosphatidic acid formation and 40 kD protein phosphorylation in the patient’s platelets, whereas these responses to thrombin were within normal ranges. 12-O-Tetradecanoyl-phorbol-13-acetate (TPA) also evoked normal response in the 40 kD protein phosphorylation in the patient’s platelets. These results suggested that the patient’s platelets had TXA2 receptor abnormalities which were characterized by defective transduction of the binding signal to postreceptor reactions after normal TXA2 binding.
Keywords: Platelet thromboxane A2 receptor; Defective signal transduction; Platelet dysfunction; Polycythemia vera